DEVELOPING WRITING RECOUNT TEXT SKILL THROUGH PICTURE SEQUENCES AT SMP NEGERI 9 PALU - Azfianty, Suzy (Paedagogia: Jurnal Pendidikan, 2016)
Developing Writing Skill through Picture Sequences at SMP Negeri 9 Palu, Central Sulawesi. This research aims at investigating the procedure and the effectiveness of picture sequences in teaching writing to the students. The students were trained to write recount texts based on picture sequences. The subject of research was grade VII C students of SMPN 9 Palu, the academic year 2013/2014 which consists of 35 students. The research took common steps of the action research; planning, acting, observing, and reflecting. This research was held in two cycles, each cycle consisted of three meetings. The researcher used observation sheet, field notes, and tests to collect the data. The result of the data analysis showed that the application of pictures sequences in teaching writing recount text is effective in cycle 2. It was proved by the number of students who got the minimum standard of individual learning achievement (65) in cycle 1 which was obtained by 13 students or 37,14 %. In cycle 2, there were 29 students or 82,86 % who have met the criterion of individual learning achievement. The percentage (82,86 %) was greater than the classical achievement. In cycle 2 criteria of the achievement in content, organization, grammar, vocabulary, and mechanic, have been achieved. The score is greater than 65.